Bioengineered gold nanoparticles targeted to mesenchymal cells from patients with bronchiolitis obliterans syndrome does not rise the inflammatory response and can be safely inhaled by rodents. Issue 4 (21st April 2017) - Cova, Emanuela; Inghilleri, Simona; Pandolfi, Laura; Morosini, Monica; Magni, Sara; Colombo, Miriam; Piloni, Davide; Finetti, Chiara; Ceccarelli, Gabriele; Benedetti, Laura; Cusella, Maria Gabriella; Agozzino, Manuela; et al.
Abstract: The use of gold nanoparticles (GNPs) as drug delivery system represents a promising issue for diseases without effective pharmacological treatment due to insufficient local drug accumulation and excessive systemic toxicity. Bronchiolitis obliterans syndrome (BOS) represents about 70% of cases of chronic lung allograft dysfunction, the main challenge to long-term lung transplantation. It is believed that due to repeated insults to epithelial bronchiolar cells local inflammatory response creates a milieu that favors epithelial–mesenchymal transition and activation of local mesenchymal cells (MCs) leading to airway fibro-obliteration. In a previous work, we engineered GNPs loaded with the mammalian target of rapamycin inhibitor everolimus, specifically decorated with an antibody against CD44, a surface receptor expressed by primary MCs isolated from bronchoalveolar lavage of BOS patients. We proved in vitro that these GNPs (GNP-HCe) were able to specifically inhibit primary MCs without affecting the bronchial epithelial cell. In the present work, we investigated the effect of these bioengineered nanoconstructs on inflammatory cells, given that a stimulating effect on macrophages, neutrophils or lymphocytes is strongly unwanted in graft airways since it would foster fibrogenesis. In addition, we administered GNP-HCe by the inhalatory route to normal mice for a preliminary assessment of their pulmonary and peripheral (liver, spleen and kidney) uptake. By these experiments, an evaluation of tissue toxicity was also performed. The present study proves that our bioengineered nanotools do not rise an inflammatory response and, under the tested inhalatory conditions that were used, are non-toxic.